Examining the Impact of Technostress on Perceived Organizational Commitment: The Mediating Role of Individual Innovation - Hessari, Hassan; Daneshmandi, Fatemeh; Nategh, Tahmineh (International Journal of Business and Applied Economics, 2024)
This research examines the influence of technostress on perceived organizational commitment (POC) and investigates how individual innovation mediates this relationship. Conducted within an engineering consulting firm, the research employs structural equation modeling (SEM) to analyze data from 147 employees. The objectives include determining the extent to which technostress influences POC, assessing how individual innovation mediates this effect, and identifying strategies to mitigate technostress impacts. Findings indicate that technostress significantly negatively affects both POC and individual innovation, with the latter showing a positive correlation with POC. Moreover, individual innovation serves as a partial mediator, mitigating the adverse effects of technostress on POC. The results highlight the necessity for organizations to foster innovative cultures while managing technostress, thus promoting a resilient and committed workforce. This study contributes to the literature by integrating the constructs of technostress, innovation, and organizational commitment, providing actionable insights for managers aiming to enhance employee engagement and organizational stability.